Qualidade das silagens de sorgo e de planta inteira de soja na terminação de cordeiros em confinamento - Protes, Verena Micheletti [UNESP] (2015)
The objective of this research was to evaluate the effect of using whole-plant soybean silage (WPSS) compared to sorghum silage (SOS) in diet for finishing crossbred lambs on performance, carcass characteristics, meat quality and economic performance. The soybean used was the BMX Power RR, sown 3 cm deep and density of 400,000 seeds / he, spaced 0.45 m. The mechanical harvesting of silage mass was done when the soybean plants reached the reproductive stage R7, the height of 10-15 cm from the ground level, using two line shelf reduced average spacing between lines of 0.50 m and the cut material into particles averaging 4 mm. The experimental design was completely randomized with two treatments and 14 repetitions, one of a conventional diet for lambs in confinement with SOS and the other with WPSS as roughage. The animals with early weight of 20 ± 2 kg were randomly assigned to each treatment, housed in individual pens with free access to the trough and water, were slaughtered when they reached the average weight of 32 kg. There was no significant difference (P <0.05) between treatments for the performance parameters, economic evaluation, carcass quality and meat, except for shear force, where the animals fed WPSS had higher meat tenderness. There was no difference for most fatty acids found in meat, except for the six fatty acids: 0, 14: 1, 20: 0; 16: 0, 16: 1 found in larger amounts in meat of sorghum treatment and fatty acid 18: 2n6c and 18: 1n9t in larger amounts in meat of soybean treatment. Animals fed with WPSS had a lower amount of acid hypercholesterolemic (16: 0, 14: 1, 16: 1) and higher concentrations of omega 6 in their meat. The WPSS can be a alternative of roughage to finishing lambs in confinement because no negative effect on animal performance, and have provided a beef with superior softness, fewer harmful acids to health and higher amounts of omega 6.